The synthesis and research of the naphthalimide G-quadruplex probe targeting hybrid G4s - Lilin Gan; Wenzheng Luo; Qian Cheng; Shanke Wan; Min Wu; Mingqi Wang; Enming Luo; Xianjin Luo; Shuo Li (Results in Chemistry)
The human C-MYC promoter and telomere G4 DNA structures were widely recognized as promising targets for cancer therapy. Nevertheless, the effectiveness of the traditional small-molecule fluorescent probe targeting G4 was hindered by limitations in single function and low selectivity, and progress in anti-tumor research was impeded. In this study, a novel naphthalimide probe（AI7）was synthesized and reported for hybrid G4 structures targeting, and 3–10 times fluorescence intensity was increased by the interaction with hybrid G4 structures. Meanwhile, the fluorescence intensity was significantly enhanced when hybrid G4 structures within the cell nucleus with AI7 were bound. S-phase DNA extracts from normal and tumor cells, there were obvious differences in fluorescence intensities when conjugated with AI7, which could distinguish each other. Herein, AI7 also showed potential anti-tumor activity and good biological compatibility.